MARKETING EFFECTIVENESS IN RELATIONSHIP WITH CUSTOMER VALUE - Mahdani Mahdani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
This paper wants to describe a theoretical study about: the factors that influence the effectiveness of marketing, analysis of the gap between sales and marketing associated with customer perceptions. The success of a company in the long term is closely linked to effective marketing. One indication of effective marketing is located in point deviation between marketing and sales. Ie deviation can be formulated sales: Sales = Sales Revenue Variance in the master budget> <Actual sales revenue. Deviations terindekasi sales to marketing effectiveness caused by aberrations in the sale price, number of sales, product mix and market share.